2018
DOI: 10.1166/jnn.2018.14537
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic Acid/Chitosan Nanoparticles Loading Nifedipine: Characterization Findings and In Vivo Investigation in Animal

Abstract: This paper presents the results of zeta potential, water contact angle, atomic force microscopy image, in vitro solubility, and content of heavy metals in polylactic acid (PLA)/chitosan (CS) nanoparticles loading nifedipine. In addition, the In Vivo test of the PLA/CS nanoparticles loading nifedipine in the mice is also one of highlights of this work. The Zeta potential result shows that the charged surface of the PLA/CS nanoparticles loading nifedipine is neutral, negative or complex depending on nifedipine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The nanoparticles had a rough surface and did not contain heavy metal ions. The swelling ability in phosphate buffer of PCN nanoparticles was better than that of PC nanoparticles [26]. The drug loading capacity of PCN nanoparticles was also determined.…”
Section: Preparation Methods and Characterization Of Emulsionsmentioning
confidence: 96%
See 2 more Smart Citations
“…The nanoparticles had a rough surface and did not contain heavy metal ions. The swelling ability in phosphate buffer of PCN nanoparticles was better than that of PC nanoparticles [26]. The drug loading capacity of PCN nanoparticles was also determined.…”
Section: Preparation Methods and Characterization Of Emulsionsmentioning
confidence: 96%
“…Besides, the intensity of the NIF crystal peaks also increased with increasing the NIF content in the nanoparticles [24]. PCN nanoparticles containing different NIF contents were hydrophilic with contact angle less than 90 o [26]. The nanoparticles had a rough surface and did not contain heavy metal ions.…”
Section: Preparation Methods and Characterization Of Emulsionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Another bio-degradable polymer used on PNPs in experimental studies of hypertension is chitosan. Chitosan, a linear polysaccharide made from the shells of crustaceans, can be formed into spherical biopolymers for the encapsulation of water insoluble drugs, including those to treat hypertension (50)(51)(52)(53). As with the other PNPs, chitosan based polymers are suggested to improve oral administration by increasing solubility of the drug.…”
Section: Antihypertensive Pnp Drug Formulations Tested In Animal Modelsmentioning
confidence: 99%
“…The emerging interest and relevance for chitosan based PNPs is evidenced by two studies published earlier this year detailing the beneficial effects of using chitosan based PNPs: Auwal et al showed that chitosan PNPs encapsulating food based antihypertensive biopeptides, a safe and thus potentially attractive source of non-pharmaceutical treatment of TRH, protect the biopeptide from gastrointenstinal degradation (50). In addition, Chinh et al showed that polylactic acid/ chitosan NPs carrying the Ca 2+ channel blocker nifedipine reduced blood pressure in mice (51).…”
Section: Antihypertensive Pnp Drug Formulations Tested In Animal Modelsmentioning
confidence: 99%